A dangerous game that may harm kids and teens: a review on synthetic cannabinoids (bonzai) - Kalyoncu, Ö. Ayhan; Ünlü, Buse; Taştan, Ufuk (Journal of Dependence, 2014)
Synthetic cannabinoid (SC), also known by the street names “Bonzai”, “fake weed”, “K2” and “Jamaika” is a highly addictive drug with numereous serious adverse effects and dangers, has been rapidly spreading especially amongst young people during the recent years. The manufacturers of this drug are constantly changing the compounds, thus creating new recipes, making it difficult to identify the pharmacological profiles of the drug sold as a SC, poses a danger for the health sector. The wrong perception that is constructed around the name Bonzai, leads the abusers of the drug into thinking that this drug is harmless; this misconseption is a reason why SC has became rapidly popular especially amongs teenagers. Plus, SC is marketed as a legal version of marijuana, therefore teens tend to use this drug without considering the dangerous consequences it may potentially lead to. The effects of SC can be clustered under mood, cognitive processes and impairments in perception. The impacts of the SC usage can be listed as the following symptoms; varying anxiety levels, paranoia, cognitive impairment, increases in heart rate, hallucinations and delusions. This review aims to introduce SCs and to exhibit the adverse effects it causes on the brain, on people’s daily lives and their functionality. By going through the PubMed database, this review is put forward after an examination of research and relevant literature according to the keywords; “synthetic marijuana”, “synthetic marijuana addiction”, and “synthetic cannabinoid”. Due to the limited number of research done on the selected topic, this review partially consists of comparisons between marijuana and SCs.
Keywords: Synthetic cannabinoids; marijuana; bonzai addiction; bonzai effects